Peptide Supramolecular Hydrogels with Sustained Release Ability for Combating Multidrug-Resistant Bacteria - Shang, Lu; Liu, Jing; Wu, Yuting; Wang, Mi; Fei, Chenzhong; Liu, Yingchun; Xue, Feiqun; Zhang, Lifang; Gu, Feng (ACS applied materials & interfaces, 2023)
Chronic wound infection caused by multidrug-resistant bacteria is a major threat globally, leading to high mortality rates and a considerable economic burden. To address it, an innovative supramolecular nanofiber hydrogel (Hydrogel-RL) harboring antimicrobial peptides was developed based on the novel arginine end-tagging peptide (Pep 6) from our recent study, triggering cross-linking. In vitro results demonstrated that Hydrogel-RL can sustain the release of Pep 6 up to 120 h profiles, which is biocompatible and exhibits superior activity for methicillin-resistant Staphylococcus aureus (MRSA) biofilm inhibition and elimination. A single treatment of supramolecular Hydrogel-RL on an MRSA skin infection model revealed formidable antimicrobial activity and therapeutic effects in vivo. In the chronic wound infection model, Hydrogel-RL promoted mouse skin cell proliferation, reduced inflammation, accelerated re-epithelialization, and regulated muscle and collagen fiber formation, rapidly healing full-thickness skin wounds. To show its vehicle property for wound infection combined therapy, etamsylate, an antihemorrhagic drug, was loaded into the porous network of Hydrogel-RL, which demonstrated improved hemostatic activity. Collectively, Hydrogel-RL is a promising clinical candidate agent for functional supramolecular biomaterials designed for combating multidrug-resistant bacteria and rescuing stalled healing in chronic wound infections.